Photocatalytic Degradation of Phenol by Thermal Titanium Dioxide Thin Layer Electrodes - Lopes, Paulo Renato Matos; Montagnolli, Renato Nallin; Bidoia, Ederio Dino (Water, air, and soil pollution, 2012)
Electrochemical processes in industrial effluents have been studied as a means to obtain higher efficiency in wastewater treatment. Heterogeneous photocatalysis appears as a low-cost alternative through the use of lower wattage lamps and thermal TiO 2 films. Photocatalysis became a clean process for water treatment due to hydroxyl radicals generated on semiconductor surface. Such radicals are able to degrade several organic compounds. This study used different electrodes and analytical methods for degradation of phenol molecules to reduce treatment costs, improve efficiency, and identify compounds formed during the decomposition of phenolic molecules. Thermal growth of TiO 2 film was observed on the titanium electrode in rutile form. Application of an electrical potential on the Ti/TiO 2 working electrode increases efficiency in reducing concentration of phenol after photocatalytic treatment. Still, high energy radiation (UVC) showed best degradation rates in photolytic process. Different compounds formed during the degradation of phenol were also identified in the UVC–PE treatment.